Comparison of Different Staging Systems Applied to a Cohort of Patients With Oral Tongue and Floor of the Mouth Cancer - Lorenzo Bresciani; Lorenzo Giannini; Alberto Paderno; Fabiola Incandela; Walter Fontanella; Davide Mattavelli; Davide Mattavelli; Cesare Piazza; Cesare Piazza (Frontiers Media S.A., 2021)
Purpose: The present work compares the effects produced by the application of the 7th edition of the tumor node metastasis (TNM) staging system (TNM7), 8th Edition (TNM8) with its two subsequent revisions, and pN-N+ classification on a cohort of patients with oral tongue and floor of the mouth cancer.Methods: A monocentric cohort of 148 patients was retrospectively analyzed. Patients were staged according to the TNM7, TNM8 and revisions, and pN-N+ classification. Stage migration was assessed and overall survival (OS) analyzed with the Kaplan-Meier method. The pT, pN, and stage stratification was evaluated with univariate and multivariate Cox regression and comparing adjacent categories with the log-rank method.Results: pT3-T4a categories showed significant differences in comparison to pT1-T2 for each staging metric employed in both uni- and multivariate analysis. When comparing adjacent pT categories, OS was significantly different only between pT2 and pT3 categories of the TNM8. Disproportionate patient distribution among pN categories was observed in the TNM8, and stratification was scarce. Conversely, in the pN-N+ classification the difference between pN2 and pN3a categories was significant. Only stage IVa reached statistical significance in TNM7, whereas stage III and above were significant in TNM8 and revisions in both uni- and multivariate analysis. However, no significant difference was noted comparing adjacent stages.Conclusion: The TNM8 pT classification differentiated low- from high-risk diseases. Nonetheless, it failed to separate pT1 from pT2 and pT3 from pT4a categories. Conversely, although TNM8 nodal staging was inaccurate, the number of metastatic lymph nodes was more valuable.